A concise guide to project collaboration : building a delivery organization - Hornby, Robin, 1945- (New York, NY : Routledge, 2023)
"Easy to read and act on immediately, this concise guide shows how organizations can work more effectively with in-house or contracted project managers and their teams, using specific collaborative techniques to improve success rates, reduce project costs and enable organizations to benefit from common-sense, cost-effective project management approaches that work. Using a clear structure and accessible style, the book demonstrates how: Managers can create an organizational environment more naturally adapted for project work and recognition of business priorities; Barriers to project work can be removed so project managers can focus on resolving real project problems; Specific collaborative project management methods engaging business owners, users, and technical teams can be illuminated and implemented; Projects can fit within an architecture that aligns with business needs using models and workflow designs; and how standardized delivery management can unify in-house and vendor teams to create a uniform and predictable owner experience. The book is aimed at managers and executives (both IT and users) in corporations and vendor firms who are engaged in delivering projects. The book will also be invaluable to any project manager or senior practitioner who is interested a business-oriented, unified, and collaborative approach to project management"--
Keywords: Project management; Business planning; Organizational change; BUSINESS & ECONOMICS / Project Management; BUSINESS & ECONOMICS / Operations Research